LIGHT USE EFFICIENCY DISTRIBUTION AS A FUNCTION OF DIFFERENT TREE SHAPES IN APPLE - Z. Q. Gao; Z. Q. Li (Journal of Animal and Plant Sciences, 2015)
Light use efficiency (LUE) is the single, most influencing factor on fruit yield and quality. The three-dimensional (3-D) distribution and diurnal variation of the LUE of the fruit tree canopy can be simulated by establishing the coupled model of the net photosynthetic rate (Pn) and the 3-d canopy’s photo synthetically-active radiation (PAR). The 3-D distribution of the Pn of the canopy was determined by the C3 photosynthesis model and the 3-D distribution of PAR and leaf area. LUE was expressed as the ratio of Pn to PAR. The diurnal variations and 3-D distributions of four apple tree shapes LUEs (I: small-sparse shape, II: disperse-stratified shape, III: spindle shape, and IV: open-center shape) were simulated through the coupled model. The results of the simulation demonstrated that, under high radiation conditions (PAR=1500 μmol·m- 2·s-1), the LUEs of the four tree shapes were 0.0186 μmol·mol-1 , 0.0199 μmol·mol-1 , 0.0187 μmol·mol-1 , and 0.0150 μmol·mol-1 , in treatment I to IV, respectively. On clear days, the apple tree canopy’s LUE displayed a bimodal curve. The LUEs of the four tree shapes’ canopies per unit of ground for a day were 0.0127 mol·mol-1 , 0.0151 mol·mol-1 , 0.0144 mol·mol-1 , and 0.0115 mol·mol-1 , in treatment I to IV, respectively. Of the four tree shapes, the average LUE of the open- center shape was the highest, being 0.0175 mol·mol-1 , and it was respectively 8.3%, 5.9%, and 5.7% higher than that of the small-sparse shape, the stratified-disperse shape, and the spindle shape. The study indicated that the 3-D distributions and diurnal variations of the LUEs of the different apple tree shapes’ 3-D canopies can be simulated through the coupled model. The results also showed that, of the four apple tree shapes, the LUE of the open- center shape was the highest, which could improve fruit quality. Also, the other three tree shapes’ canopies had high total amounts of LUE, which could raise fruit yield.
Keywords: Apple; Tree shape; Light use efficiency; Photosynthetically active radiation; Model; Photosynthesis